Energy Services Analysis An Alternative Approach for Identifying Opportunities to Reduce Emissions of Greenhouse Gases - Crane, Keith (RAND Corporation, 2012)
Most environmental analyses focus on changing existing processes to use less energy and produce fewer emissions. This report uses energy service analysis (ESA) to examine possibilities for instead changing how a service is delivered. The ESA framework is used to analyze how changes in the provision of two services-news delivery and personal mobility-might reduce greenhouse-gas emissions and suggests other areas in which ESA could be applied.